Enhancing Physics Conceptual Understanding through Discussion Method and Virtual Laboratory Media: A Classroom Action Research on Light and Optical Instruments - Setiahawati; Diah Setiani; Winda Nur Khasanah (ISEJ : Indonesian Science Education Journal, 2024)
The mastery of physics concepts among junior high school students remains a challenge, particularly in topics that involve abstract phenomena such as light and optical instruments. This study aimed to improve students’ conceptual understanding and learning motivation through the integration of the discussion method and virtual laboratory media. A classroom action research (CAR) design was employed in two cycles, each consisting of planning, implementation, observation, and reflection stages, conducted with 35 eighth-grade students at SMP Al-Kindi Cipayung. Data were collected using tests, questionnaires, and observations, while results were analyzed descriptively through mean scores and mastery percentages. The findings showed a steady increase in student learning outcomes, with mastery achievement improving from 31.42% in the pre-cycle to 60% in the first cycle and 91.42% in the second cycle. Students also reported positive responses to the use of virtual laboratories, noting their role in clarifying complex concepts, enhancing interaction, and creating a more engaging learning environment. The novelty of this study lies in combining collaborative discussion with digital simulation, offering an alternative pedagogical strategy to compensate for limited physical laboratory resources. These results imply that integrating traditional discussion with virtual laboratories can serve as an effective approach to foster conceptual understanding, critical thinking, and motivation in physics learning, and that broader implementation across schools could enhance the quality of science education in resource-constrained settings.